Frankish Bread and Baking Ovens in the Latin Kingdom of Jerusalem: Between Conservatism and Adaptation. Issue 2 (3rd July 2022) - Yehuda, Elisabeth; Bronstein, Judith; Stern, Edna J.
Abstract : THIS ARTICLE EXAMINES THE TOPIC OF BREAD and bread-making in the Latin Kingdom of Jerusalem. Drawing on archaeological evidence, historical sources, and medieval illuminations, we consider three features closely: the types of bread consumed by the Franks, the baking ovens' appearance and modes of operation, and the organisation of Frankish bread production. We then set out to position Frankish baking in its proper cultural context between western Europe, whence the Franks originate, and the southern Levant, their new home. In doing so, we aim to uncover the novelties of Frankish baking, possible transfers of technology and ultimately the origin of Frankish baking ovens. By closely examining all available material, we strive to reveal peculiarities and influences that shaped bread making in the Latin Kingdom of Jerusalem.